Beyond Peer Cyberbullying – Involvement of Polish Adolescents in Different Kinds of Electronic Aggression - Pyżalski, Jacek (Wydawnictwo Naukowe UAM, 2013)
Cyberbullying is often defi ned as aggression conducted through mobile phones and the Internet. This phenomenon is predominantly understood as a kind of peer aggression, when both the perpetrator(s) and the victim belong to the same group (class or online community). However, the Internet extends and facilitates harassment not only of peers. The paper focuses on different kinds of electronic aggression identifi ed through qualitative research (interview, e-mail interviews and focus groups with students and teachers). The results have shown that except cyberbullying one can indicate fi ve further types of electronic aggression. They are: aggression against celebrities (e.g. actors, singers, etc.), aggression against the vulnerable (e.g. alcoholics, etc.), aggression against school staff, aggression against groups/ideas (when the victim is not a particular, identifi able person) and free-fl oating (random) aggression (often when the victim is totally anonymous to the perpetrator). This typology has been positively verifi ed in a survey on a representative sample of Polish adolescents (N = 2143). The paper presents the typology with the examples from the qualitative stage of research, also discussing potential socialization risks for each kind of electronic aggression. It shows also (on the basis of quantitative research) the prevalence of perpetration and victimization of different kinds of electronic aggression as well as their co-occurrence. It demonstrates the factors that infl uence such involvement. It must be stated that although peer aggression cyberbullying seems to be predominant, other kinds of electronic aggression have also been frequently conducted by the respondents. For example, a signifi cant percentage of perpetrators attacked through new media the following groups of victims: random Internet users (30.3%), groups of people (19.7%), celebrities (13.9%), and vulnerable victims (13.3%). The conclusions underline the need to extend prevention educational tools to different kinds of electronic aggression, not restricting them to cyberbullying understood as an extension of traditional bullying.
Nie tylko mobbing elektroniczny – zaangażowanie polskich nastolatków w różne rodzaje agresji elektronicznej
Keywords: cyberbullying; electronic aggression; adolescents; ICT; computer-mediated communication